Improving electricity market model for Malaysia electric supply industry - Nurehan Othman, Nurehan (2014)
As one of the developing countries, Malaysia has been working on regulatory frameworks and trading arrangement to create more competition in the Malaysia Electricity Supply Industry (MESI) environment. Malaysia has applied single buyer model as its electricity market model since 2001 with Tenaga Nasional Berhad (TNB) responsible in generation, transmission and distribution. However, TNB alone is unable to cater the growth in electricity demand due to rapid development of national economy. Therefore, Malaysia has taken an immense step in MESI by permitting Independent Power Producer (IPPs) to participate in the generation sector. The IPPs and TNB have signed a Power Purchase Agreement (PPA) in which TNB agreed to pay payment for availability to the IPPs regardless of the usage of power generated. The long term PPA caused TNB to suffer massive profit loss due to the capacity payment. The adoption of pool market in MESI will cause high cost IPPs to lose the opportunity to be included in generation dispatch and eventually lose the revenue at low electricity demand. Conversely, the System Marginal Price (SMP) that cleared the market will become too high at peak electricity demand, providing excessive revenue for low cost IPPs. This thesis proposes two electricity markets for MESI. The hybrid market is developed from the original pool market with addition of demand sharing and capacity payment approaches. The second electricity market proposes a single buyer market with fraction capacity payment. The IEEE 14 bus, IEEE 30 bus, Reliability Test System 1996 (Rts96) and Malaysia electricity system were used to illustrate the merit of both proposed markets. Results have shown that hybrid market proposed in this thesis ensures IPPs’ participation and provides continuous revenue for all IPPs even at the lowest demand. Meanwhile, the proposed single buyer model has successfully reduced approximately 15.25% of total capacity payment paid by TNB to the IPPs